Sociopsychological correlates of militant extremist beliefs in a postconflict society: The importance of ethnocentrism and quality of interethnic contacts. (December 2020) - Stankov, Lazar; Međedović, Janko; Lazarević, Ljiljana B.; Petrović, Boban; Knežević, Goran
This study investigates the attitudinal and motivational bases of militant extremist beliefs in a postconflict society ( N = 600; 51% female). Militant extremist mindset (MEM) measures of proviolence, divine power, utopianism, vile world, and West, together with the Ethos of Conflict- Grudge Scale (EOC-grudge), were used to assess militant-extremist beliefs. Data about the socioeconomic status (SES) of participants, ethnocentrism, intergroup contact, trust in the system, and the level of conflict in the sampled areas were also collected. The main hypotheses were that extremist beliefs are associated with a high level of ethnocentrism, low socioeconomic status, decreased intergroup contact, low trust in the system, and recent intergroup conflict. A structural model in which all relations between the measures were simultaneously tested showed that recent intergroup conflict was related to the most malignant aspect of MEM—proviolence—predominantly through negative experiences with members of other ethnicities. Ethnocentrism was strongly related to higher levels of grudge and excuse. Self-assessed socioeconomic status was related to grudge only but taking into account all other variables, positively. Finally, trust in the political and social system was not found to have a relationship with militant-extremist beliefs.